Application of amorphous zirconium (hydr)oxide/MgFe layered double hydroxides composite in fixed-bed column for phosphate removal from water - A. Nuryadin; T. Imai (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Fixed-bed column has been considered an industrially feasible technique for phosphate removal from water. Besides the adsorption capacity, the effectiveness of an adsorbent is also determined by its reusability efficiency. In this study, phosphate removal by a synthesized amorphous zirconium (hydr)oxide/MgFe layered double hydroxides composite in a fixed-bed column system was examined.  METHODS: The effects of flow rate, bed height, phosphate concentration, solution pH, and adsorbent particle size on the phosphate adsorption ability were examined through a series of continuous adsorption experiments. The appropriate breakthrough curve models, phosphate adsorption from real anaerobic sludge and synthetic seawater, column regeneration and reusability, and adsorption mechanism were also investigated for practical application feasibility.  FINDINGS: The results showed that the increased bed height and phosphate concentration, and reduced flow rate, pH, and adsorbent particle size were found to increase the column adsorption capacity. The optimum adsorption capacity of 25.15 mg-P/g was obtained at pH 4. The coexistence of seawater ions had a positive effect on the phosphate adsorption capacity of the composite. Nearly complete phosphate desorption, with a desorption efficiency of 91.7%, could be effectively achieved by 0.1 N NaOH for an hour. Moreover, the initial adsorption capacity was maintained at approximately 83% even after eight adsorption-desorption cycles, indicating that the composite is economically feasible. The high phosphate adsorption capacity of the composite involves three main adsorption mechanisms, which are electrostatic attraction, inner-sphere complexation, and anion exchange, where the amorphous zirconium hydr(oxide) on the surface of the layered double hydroxides likely increased the number of active binding sites and surface area for adsorption.  CONCLUSION: The amorphous zirconium (hydr)oxide/MgFe layered double hydroxides composite, with its high adsorption capacity and superior reusability, has the potential to be utilized as an adsorbent for phosphorus removal in practical wastewater treatment. This study provides insights into the design of amorphous zirconium (hydr)oxide/MgFe layered double hydroxides composite for phosphorus removal and recovery in a practical system. ==========================================================================================COPYRIGHTS©2021 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers.==========================================================================================